Reframing Heritage Change: Applying the Limits of Acceptable Change (LAC) Framework to Stakeholder Perceptions in the Heritage Area of Jakarta Historic District - Widhi, Frianty Kartika; Eddyono, Fauziah (Yayasan Sinergi Kawula Muda, 2026)
This study explores stakeholder perceptions of physical, social, and cultural changes in the Core Zone of the Jakarta Historic District using the Limits of Acceptable Change (LAC) framework. As a major urban heritage destination experiencing increasing tourism pressure, the area faces challenges related to authenticity, social dynamics, and environmental quality. A qualitative approach was employed through in-depth interviews with key stakeholders, including heritage managers, local communities, and business actors, supported by thematic analysis using NVivo. The findings indicate that while physical improvements and increased visitation are generally perceived positively, stakeholders express concerns regarding crowding, socio-cultural shifts, and the gradual loss of community space. Rather than defining fixed thresholds, the study proposes qualitative indications of acceptable change based on stakeholder perceptions, particularly in relation to visitor density, environmental conditions, and socio-cultural dynamics. This study contributes by adapting the LAC framework to a living urban heritage context through multi-stakeholder qualitative evidence, highlighting the role of socio-cultural indicators and community space as critical dimensions of acceptable change. The findings also inform context-sensitive management strategies, including visitor regulation, cultural space protection, and participatory governance, to support more sustainable heritage tourism management.